(untitled) (Gestionar: revista de empresa y gobierno, 2021)
This work aims to determine the concept of code in the poem “A un Médico Tuerto” by Juan del Valle and Caviedes from the perspective of the analysis of poetic discourse. This investigation belongs to the qualitative and descriptive approach. The method used to analyze hermeneutics and, as a technique, poetic speech analysis encompassed the textual, enunciative, semiotic, and pragmatic dimensions. As a result, it is inferred that the action of benefiting the vulnerability of the people for personal benefit.